Locomotion Reveals Contrasting Responses in Body Mass‐Scaling of Metabolic Rates Between Winged and Wingless Arthropods - Vojsava Gjoni; Hanrong Tan; Andrew G. Hirst; Pavel Kratina; David Atkinson (Ecology Letters, 2025)
Metabolism fuels fundamental biological processes and commonly scales with body mass with an exponent, b , between 2/3 and 1. We, here, explore how differences in physical activity can reveal contrasting interspecific metabolic scaling between major groups of arthropods. The Metabolic‐level Boundaries Hypothesis predicts that increased behavioural activity increases b . We test this hypothesis by comparing b during flight, non‐flight locomotion, and rest in winged and wingless insects, and spiders. We find that interspecific b values increase with activity only with flight in winged insects which co‐occurs with a substantial flight‐related rise in metabolic level. Spiders show a shallower interspecific metabolic scaling relative to insects, potentially reflecting slower life‐history strategies with increasing body size. Consequently, large resting or walking insects consume 6–15 times more oxygen than do spiders of corresponding size and activity level. These fundamental differences offer new insights into the evolutionary dynamics of arthropod energetics.

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

Rapid assessments accurately identify threatened Australian flora under IUCN Red List Criteria after megafires - Tom Le Breton; Mark K.J. Ooi; Sylvia Hay; Joe Atkinson; Doug Bickerton; Stephanie Cerato; Richard J.P. Davies; Chantelle Doyle; Rachael Gallagher; Bettina Ignacio; David Keith; Mellissa McCallum; et al. (Biological Conservation, 2025)

Which Body Size Metrics Should Be Used for Assessing Temperature Impacts on Fish Growth and Size? - Asta Audzijonyte; Ken H. Andersen; David Atkinson; Jennifer S. Bigman; Julia L. Blanchard; Amy R. Coghlan; Freddie Heather; Max Lindmark; John R. Morrongiello; Daniel Pauly (Global Change Biology, 2025)
An extensive literature and debate exist on how and why temperature impacts animal, and especially ectotherm, body sizes. However, there remain considerable discrepancies and misunderstandings in the key definitions and concepts of body size used to describe observed temperature impacts across studies. For fish and other animals that continue growing throughout life, body size can be defined as size‐at‐maturity, adult size, asymptotic size, maximum observed size, population‐averaged length or mass, or average size‐at‐(arbitrary)‐age. These concepts of size are not equivalent, and temperature is likely to affect each in different ways. Some disagreement about temperature impacts on fish body sizes might relate to the different body size and growth metrics used, especially when combined with different biological scales (individual, population, or community) and empirical contexts (laboratory, field). Here, we review six common confusions associated with the measurement of “size” in fish and other water‐breathing ectotherms and recommend consistent and accurate use of terms and methodology to ensure that studies of global warming impacts on fish sizes can be compared and interpreted unequivocally.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Mind the gap - The need to integrate novel plankton methods alongside ongoing long-term monitoring - Matthew M. Holland; Luis Felipe Artigas; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Dafne Eerkes-Medrano; Marie Johansen; David G. Johns; Margarita Machairopoulou; Sophie Pitois; James Scott; et al. (Ocean & Coastal Management, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Construction and validation of an infant chest phantom for paediatric computed tomography - Seonaid Rodgers; Janette Atkinson; David Cryer; Cameron Storm; Rikki Nezich; Martin A. Ebert; Pejman Rowshanfarzad (Physical and Engineering Sciences in Medicine, 2024)
Paediatric imaging protocols should be carefully optimised to maintain the desired image quality while minimising the delivered patient dose. A paediatric chest phantom was designed, constructed and evaluated to optimise chest CT examinations for infants. The phantom was designed to enable dosimetry and image quality measurements within the anthropomorphic structure. It was constructed using tissue equivalent materials to mimic thoracic structures of infants, aged 0–6 months. The phantom materials were validated across a range of diagnostic tube voltages with resulting CT numbers found equivalent to paediatric tissues observed via a survey of clinical paediatric chest studies. The phantom has been successfully used to measure radiation dose and evaluate various image quality parameters for paediatric specific protocols.

Herbal leys have no effect on soil porosity, earthworm abundance, and microbial community composition compared to a grass-clover ley in a sheep grazed grassland after 2-years - Emily C. Cooledge; Craig J. Sturrock; Brian S. Atkinson; Sacha J. Mooney; Francesca L. Brailsford; Daniel V. Murphy; Jonathan R. Leake; David R. Chadwick; Davey L. Jones (Agriculture, Ecosystems & Environment, 2024)

Long‐term shifts in phenology, thermal niche, population size, and their interactions in marine pelagic copepods - Stefano Corona; Andrew G. Hirst; David Atkinson; Jasmin Renz; Maarten Boersma; Angus Atkinson (Limnology and Oceanography, 2024)
Under climatic warming many species shift their seasonal timing of life cycle events (phenology) and seasonal abundance distribution, but whether they maintain the same thermal niche is still poorly understood. Here, we studied multidecadal trends in abundance and phenology of seven major copepod species across three stations (Stonehaven (SH), Helgoland Roads (HR), and Plymouth L4) on the North–West European shelf, spanning ~ 6.5° of latitude. All seven species consistently occupied colder temperatures at the northern station compared to the southerly station, but they maintained the same realized thermal niche over years. Expected phenological shifts (i.e., earlier when warmer) in some stations were obscured possibly by the long‐term drop of copepod density in spring–summer, which may be due to a variation in the food/predators abundance. The ongoing spring–summer declines in abundance (~ 50%) of many North Atlantic pelagic species over the last five decades, as found in recent studies, may have also influenced the metrics of seasonal timing. To separate the seasonal timing of life events from that of seasonal abundance distribution, we used a time series of egg production rate (EPR) of Calanus helgolandicus at L4, and found that this shifted later into the summer–autumn over the last 30 yr of warming, coincident with declining spring–summer food and increasing predator abundance. Overall, direct temperature effects do appear to influence the seasonal timing of the copepods, but to explain impacts at individual stations or long‐term trends in population size or phenology, understanding the changing balance of food and predators appears to be critical.

Responses of intraspecific metabolic scaling to temperature and activity differ between water‐ and air‐breathing ectothermic vertebrates - Guillermo García‐Gómez; Andrew G. Hirst; Matthew Spencer; David Atkinson (Ecology Letters, 2024)
Metabolism underpins all life‐sustaining processes and varies profoundly with body size, temperature and locomotor activity. A current theory explains some of the size‐dependence of metabolic rate (its mass exponent, b ) through changes in metabolic level ( L ). We propose two predictive advances that: (a) combine the above theory with the evolved avoidance of oxygen limitation in water‐breathers experiencing warming, and (b) quantify the overall magnitude of combined temperatures and degrees of locomotion on metabolic scaling across air‐ and water‐breathers. We use intraspecific metabolic scaling responses to temperature (523 regressions) and activity (281 regressions) in diverse ectothermic vertebrates (fish, reptiles and amphibians) to show that b decreases with temperature‐increased L in water‐breathers, supporting surface area‐related avoidance of oxygen limitation, whereas b increases with activity‐increased L in air‐breathers, following volume‐related influences. This new theoretical integration quantitatively incorporates different influences (warming, locomotion) and respiration modes (aquatic, terrestrial) on animal energetics.

Global synthesis reveals strong multifaceted effects of eucalypts on soils - Max Mallen‐Cooper; Joe Atkinson; Zoe A. Xirocostas; Baptiste Wijas; Giancarlo M. Chiarenza; Frederick A. Dadzie; David J. Eldridge (Global Ecology and Biogeography, 2022)
Aim Eucalypts have a widespread global distribution owing to their popularity for agroforestry and as environmental plantings. Despite an abundance of site‐specific evidence that eucalypts modify soils and soil processes, we lack a quantitative synthesis of their overall effects at the global scale. This limits our capacity to assess the likely impacts of future introductions in any given region of the world. Location Global. Time period 1986–2021. Major taxa studied Eucalyptus , Angophora and Corymbia . Methods We used a systematic search to derive a database of empirical data from 227 studies across 33 countries ( n effect size = 2,806) and tested three predictions about the effects of eucalypts on soil properties and whether these effects varied with plantation age and soil depth. Results Compared with (non‐eucalypt) native vegetation, eucalypts significantly reduced soil moisture, microbial abundance, nitrogen, cations and anions. Relative reductions in soil microbes and ions were stronger in older eucalypt plantations. A comparison of eucalypts with (non‐eucalypt) silvicultural and agropastoral systems revealed similar effects on most soil properties, although eucalypts tended to reduce potassium and enhance carbon to a greater extent than other managed systems. We found no consistent effects of eucalypts on soil pH. Main conclusions Our study provides the first extensive global meta‐analysis of the effects of eucalypts on soil properties and processes and demonstrates that effects are highly dependent on the community with which they are compared (i.e., natural or managed). In general, our findings reinforce the widely held belief that eucalypts deplete soil nutrients and dominate water resources. Understanding how eucalypts affect soils allows us to assess their global suitability for agroforestry, soil rehabilitation and soil carbon enhancement, while considering the potential environmental costs.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Density‐dependent modulation of copepod body size and temperature–size responses in a shelf sea - Stefano Corona; Andrew Hirst; David Atkinson; Angus Atkinson (Limnology and Oceanography, 2021)
Body size is a fundamental trait in ecology, and body size reduction with increasing temperature has been termed the third universal response to climate warming. Although effects of temperature and food on phenotypic plasticity of zooplankton adult body size have been investigated, density‐dependent effects have been neglected. We measured seasonal changes in the prosome length of 7098 adult females of 7 dominant copepod species in 13 yr spanning a 27‐yr period of warming at the L4 time series off Plymouth, UK. The seasonal temperature–size (T–S) response varied greatly among species, from reductions of 2.93% of carbon mass °C −1 for Paracalanus parvus to 10.15% of carbon mass °C −1 for Temora longicornis . Evidence for a long‐term T–S response was detected in at least two species, supporting the hypothesis that climatic warming leads to smaller adult sizes. April was a crucial month for determining the strength of the T–S response. During this month, body size related negatively to total zooplankton abundance. We suggest that the mechanism for this density dependence is via competition for food and/or intraguild predation, since spring was also the period when the ratio of food biomass to zooplankton biomass was at its lowest. Our study is among the first in situ demonstrations of density‐dependent effects on the body size of marine zooplankton and shows the need to consider the effect of top‐down as well as bottom‐up factors on body size in a warming climate.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Chronically elevated depressive symptoms interact with acute increases in inflammation to predict worse neurocognition among people with HIV - Rowan Saloner; Emily W. Paolillo; Robert K. Heaton; David J. Grelotti; Murray B. Stein; Andrew H. Miller; J. Hampton Atkinson; Scott L. Letendre; Ronald J. Ellis; Igor Grant; Jennifer E. Iudicello; David J. Moore (Journal of NeuroVirology, 2021)

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Effects of anthropogenic subsidy and glyphosate on macroinvertebrates in streams - Hongyong Xiang; Yixin Zhang; David Atkinson; Raju Sekar (Environmental Science and Pollution Research, 2020)

Lifeform indicators reveal large‐scale shifts in plankton across the North‐West European shelf - Jacob Bedford; Clare Ostle; David G. Johns; Angus Atkinson; Mike Best; Eileen Bresnan; Margarita Machairopoulou; Carolyn A. Graves; Michelle Devlin; Alex Milligan; Sophie Pitois; Adam Mellor; et al. (Global Change Biology, 2020)
Increasing direct human pressures on the marine environment, coupled with climate‐driven changes, is a concern to marine ecosystems globally. This requires the development and monitoring of ecosystem indicators for effective management and adaptation planning. Plankton lifeforms (broad functional groups) are sensitive indicators of marine environmental change and can provide a simplified view of plankton biodiversity, building an understanding of change in lower trophic levels. Here, we visualize regional‐scale multi‐decadal trends in six key plankton lifeforms as well as their correlative relationships with sea surface temperature (SST). For the first time, we collate trends across multiple disparate surveys, comparing the spatially and temporally extensive Continuous Plankton Recorder (CPR) survey (offshore) with multiple long‐term fixed station‐based time‐series (inshore) from around the UK coastline. These analyses of plankton lifeforms showed profound long‐term changes, which were coherent across large spatial scales. For example, ‘diatom’ and ‘meroplankton’ lifeforms showed strong alignment between surveys and coherent regional‐scale trends, with the 1998–2017 decadal average abundance of meroplankton being 2.3 times that of 1958–1967 for CPR samples in the North Sea. This major, shelf‐wide increase in meroplankton correlated with increasing SSTs, and contrasted with a general decrease in holoplankton (dominated by small copepods), indicating a changing balance of benthic and pelagic fauna. Likewise, inshore‐offshore gradients in dinoflagellate trends, with contemporary increases inshore contrasting with multi‐decadal decreases offshore (approx. 75% lower decadal mean abundance), urgently require the identification of causal mechanisms. Our lifeform approach allows the collation of many different data types and time‐series across the NW European shelf, providing a crucial evidence base for informing ecosystem‐based management, and the development of regional adaptation plans.

Behavioral repertoire assessment of Bengal tigers (Panthera tigris) with focus on thermoregulatory behavior - Judith A. Stryker; Jim L. Atkinson; Robert D. Brown; David Barney; J. Andy B. Robinson; Jay Duncan; Esther J. Finegan (International Journal of Biometeorology, 2019)

A synthesis of major environmental-body size clines of the sexes within arthropod species - Curtis R. Horne; Andrew G. Hirst; David Atkinson (Oecologia, 2019)

Recent shoreline evolution and beach erosion along the central Adriatic coast of Italy: the case of Molise region - Carmen M. Rosskopf; Gianluigi Di Paola; David E. Atkinson; Germán Rodríguez; Ian J. Walker (Journal of Coastal Conservation, 2018)

Modelling the distribution of hard seabed using calibrated multibeam acoustic backscatter data in a tropical, macrotidal embayment: Darwin Harbour, Australia - P. Justy W. Siwabessy; Maggie Tran; Kim Picard; Brendan P. Brooke; Zhi Huang; Neil Smit; David K. Williams; William A. Nicholas; Scott L. Nichol; Ian Atkinson (Marine Geophysical Research, 2018)

Localised cutaneous microvascular adaptation to exercise training in humans - Ceri L. Atkinson; Howard H. Carter; Dick H. J. Thijssen; Gurpreet K. Birk; N. Timothy Cable; David A. Low; Floortje Kerstens; Iris Meeuwis; Ellen A. Dawson; Daniel J. Green (European Journal of Applied Physiology, 2018)

The sensitivity of breeding songbirds to changes in seasonal timing is linked to population change but cannot be directly attributed to the effects of trophic asynchrony on productivity - Samantha E. Franks; James W. Pearce‐Higgins; Sian Atkinson; James R. Bell; Marc S. Botham; Tom M. Brereton; Richard Harrington; David I. Leech (Global Change Biology, 2018)
A consequence of climate change has been an advance in the timing of seasonal events. Differences in the rate of advance between trophic levels may result in predators becoming mismatched with prey availability, reducing fitness and potentially driving population declines. Such “trophic asynchrony” is hypothesized to have contributed to recent population declines of long‐distance migratory birds in particular. Using spatially extensive survey data from 1983 to 2010 to estimate variation in spring phenology from 280 plant and insect species and the egg‐laying phenology of 21 British songbird species, we explored the effects of trophic asynchrony on avian population trends and potential underlying demographic mechanisms. Species which advanced their laying dates least over the last three decades, and were therefore at greatest risk of asynchrony, exhibited the most negative population trends. We expressed asynchrony as the annual variation in bird phenology relative to spring phenology, and related asynchrony to annual avian productivity. In warmer springs, birds were more asynchronous, but productivity was only marginally reduced; long‐distance migrants, short‐distance migrants and resident bird species all exhibited effects of similar magnitude. Long‐term population, but not productivity, declines were greatest among those species whose annual productivity was most greatly reduced by asynchrony. This suggests that population change is not mechanistically driven by the negative effects of asynchrony on productivity. The apparent effects of asynchrony on population trends are therefore either more likely to be strongly expressed via other demographic pathways, or alternatively, are a surrogate for species' sensitivity to other environmental pressures which are the ultimate cause of decline.

Representation of mid‐latitude North American coastal storm activity by six global reanalyses - Katherine A. Pingree‐Shippee; Francis W. Zwiers; David E. Atkinson (International Journal of Climatology, 2018)
Extratropical cyclones often produce extreme and hazardous weather conditions, such as high winds, heavy precipitation, blizzard conditions, and flooding, all of which have detrimental environmental/physical and socio‐economic impacts. Furthermore, storm interaction with the ocean produces additional hazards, with major local impacts, including inundation and coastal erosion. The North American west coast is influenced by the North Pacific storm track and by ‘atmospheric river’ events while the east coast is particularly influenced by winter storms that track along two favoured routes: the St. Lawrence Valley and the Eastern Seaboard. Reanalysis provides an invaluable tool for studying the characteristics of storm events that are identified as causing the most severe impacts. However, reanalysis products differ substantially in spatial resolution, model physics, assimilation approach, and the data that are assimilated. This study evaluates the representation of storm activity along the mid‐latitude North American coastlines by six global reanalyses: NCEP‐1, NCEP‐2, ERA‐Interim, Modern‐Era Retrospective analysis for Research and Applications (MERRA), Climate Forecast System Reanalysis (CFSR), and Twentieth Century Reanalysis Version 2 (20CR). Storm activity representation is evaluated at annual and seasonal timescales (JFM, AMJ, JAS, OND, and ‘extended winter’ ONDFM) during the 1979–2010 time period through comparison with selected meteorological stations using single‐point surface pressure‐based proxies of extratropical storm activity. Stations are selected on the basis of record length, reporting frequency, coastal proximity, and relatively uniform spatial distribution. Comparisons are made using data extracted from the reanalysis grid box centre that is closest to each selected station. All reanalyses are found to successfully represent most aspects of mid‐latitude North American coastal strong storm activity, annually and seasonally, along both coasts. Nevertheless, ERA‐Interim, MERRA, and CFSR provide the better representations of mid‐latitude North American coastal strong storm activity, with ERA‐Interim performing best overall.

NiftyPET: a High-throughput Software Platform for High Quantitative Accuracy and Precision PET Imaging and Analysis - Pawel J. Markiewicz; Matthias J. Ehrhardt; Kjell Erlandsson; Philip J. Noonan; Anna Barnes; Jonathan M. Schott; David Atkinson; Simon R. Arridge; Brian F. Hutton; Sebastien Ourselin (Neuroinformatics, 2018)

ENSO climate risk: predicting crop yield variability and coherence using cluster-based PCA - Weixun Lu; David E. Atkinson; Nathaniel K. Newlands (Modeling Earth Systems and Environment, 2017)

Oxidative discolouration in whole-head and cut lettuce: biochemical and environmental influences on a complex phenotype and potential breeding strategies to improve shelf-life - Paul J. Hunter; Laura D. Atkinson; Laura Vickers; Stella Lignou; Maria Jose Oruna-Concha; David Pink; Paul Hand; Guy Barker; Carol Wagstaff; James M. Monaghan (Euphytica, 2017)
Lettuce discolouration is a key post-harvest trait. The major enzyme controlling oxidative discolouration has long been considered to be polyphenol oxidase (PPO) however, levels of PPO and subsequent development of discolouration symptoms have not always correlated. The predominance of a latent state of the enzyme in plant tissues combined with substrate activation and contemporaneous suicide inactivation mechanisms are considered as potential explanations for this phenomenon. Leaf tissue physical properties have been associated with subsequent discolouration and these may be influenced by variation in nutrient availability, especially excess nitrogen and head maturity at harvest. Mild calcium and irrigation stress has also been associated with a reduction in subsequent discolouration, although excess irrigation has been linked to increased discolouration potentially through leaf physical properties. These environmental factors, including high temperature and UV light intensities, often have impacts on levels of phenolic compounds linking the environmental responses to the biochemistry of the PPO pathway. Breeding strategies targeting the PAL and PPO pathway biochemistry and environmental response genes are discussed as a more cost-effective method of mitigating oxidative discolouration then either modified atmosphere packaging or post-harvest treatments, although current understanding of the biochemistry means that such programs are likely to be limited in nature and it is likely that they will need to be deployed alongside other methods for the foreseeable future.

Identification and classification of storm surge events at Red Dog Dock, Alaska, 2004–2014 - Adam J. Wicks; David E. Atkinson (Natural Hazards, 2017)

Information infrastructure for Australia’s Integrated Marine Observing System - Marton G. Hidas; Roger Proctor; Natalia Atkins; Julian Atkinson; Laurent Besnard; Peter Blain; Philip Bohm; Jon Burgess; Kim Finney; Dan Fruehauf; Guillaume Galibert; Xavier Hoenner; et al. (Earth Science Informatics, 2016)

A global synthesis of seasonal temperature–size responses in copepods - Curtis R. Horne; Andrew G. Hirst; David Atkinson; Aitana Neves; Thomas Kiørboe (Global Ecology and Biogeography, 2016)
Aim Body size is a master trait with significant ecological importance. Seasonal changes in body size within diverse ectothermic species can result from different environmental conditions experienced during ontogeny in subsequent generations. Whilst intraspecific changes in adult size have been well studied under controlled experimental conditions and across geographical ranges, comprehensive analyses of temporal changes are lacking, and there remains considerable unexplained variation in body size responses within aquatic taxa. Using planktonic copepods as an exemplar taxon, we quantify variation in adult body mass within seasonally varying marine and freshwater environments. We describe how size variation relates to temperature, food concentration (chlorophyll‐ a ) and life‐history characteristics, including feeding strategy. Location Global. Methods Using a meta‐analytic approach we extract quantitative data from published literature on seasonal size responses of copepods. We analyse competing models to determine the best predictors of these responses, and compare the relative importance of temperature and chlorophyll‐ a concentration in explaining variation in body size. Results We quantify 140 seasonal size responses from 33 different global locations, representing 48 planktonic copepod species from four taxonomic orders. We find that temperature ( r 2 = 0.50), rather than food ( r 2 = 0.22), is the dominant explanatory variable of changes in adult body size across seasons. A striking outcome is that calanoid copepods, which utilize feeding currents to capture prey, exhibit a four‐fold greater reduction in adult body mass per °C (−3.66%) compared with cyclopoid copepods (−0.91%), which are ambush feeders. By contrast, species body size or reproductive strategy did not explain variation in the seasonal temperature–size response. Main conclusions Our findings lead us to suggest that feeding strategies may play a significant role in dictating the magnitude of seasonal temperature–size responses in copepods, with potential implications for other ectotherms with diverse feeding methods. Seasonal temperature–size responses were typically much more variable than responses in laboratory studies that provided excess food, suggesting that field conditions modify the temperature–size response.

NiftyFit: a Software Package for Multi-parametric Model-Fitting of 4D Magnetic Resonance Imaging Data - Andrew Melbourne; Nicolas Toussaint; David Owen; Ivor Simpson; Thanasis Anthopoulos; Enrico De Vita; David Atkinson; Sebastien Ourselin (Neuroinformatics, 2016)

Fine spatial resolution residential land-use data for small-area population mapping: a case study in Riyadh, Saudi Arabia - Mohammed Alahmadi; Peter Atkinson; David Martin (International Journal of Remote Sensing, 2015)

Expression of a cystatin transgene can confer resistance to root lesion nematodes in Lilium longiflorum cv. ‘Nellie White’ - Paulo Vieira; Sarah Wantoch; Catherine J. Lilley; David J. Chitwood; Howard J. Atkinson; Kathryn Kamo (Transgenic Research, 2015)

Temperature‐size responses match latitudinal‐size clines in arthropods, revealing critical differences between aquatic and terrestrial species - Curtis R. Horne; Andrew. G. Hirst; David Atkinson (Ecology Letters, 2015)
Two major intraspecific patterns of adult size variation are plastic temperature‐size (T‐S) responses and latitude‐size (L‐S) clines. Yet, the degree to which these co‐vary and share explanatory mechanisms has not been systematically evaluated. We present the largest quantitative comparison of these gradients to date, and find that their direction and magnitude co‐vary among 12 arthropod orders ( r 2 = 0.72). Body size in aquatic species generally reduces with both warming and decreasing latitude, whereas terrestrial species have much reduced and even opposite gradients. These patterns support the prediction that oxygen limitation is a major controlling factor in water, but not in air. Furthermore, voltinism explains much of the variation in T‐S and L‐S patterns in terrestrial but not aquatic species. While body size decreases with warming and with decreasing latitude in multivoltine terrestrial arthropods, size increases on average in univoltine species, consistent with predictions from size vs. season‐length trade‐offs.

Body shape shifting during growth permits tests that distinguish between competing geometric theories of metabolic scaling - Andrew G. Hirst; Douglas S. Glazier; David Atkinson (Ecology Letters, 2014)
Metabolism fuels all of life's activities, from biochemical reactions to ecological interactions. According to two intensely debated theories, body size affects metabolism via geometrical influences on the transport of resources and wastes. However, these theories differ crucially in whether the size dependence of metabolism is derived from material transport across external surfaces, or through internal resource‐transport networks. We show that when body shape changes during growth, these models make opposing predictions. These models are tested using pelagic invertebrates, because these animals exhibit highly variable intraspecific scaling relationships for metabolic rate and body shape. Metabolic scaling slopes of diverse integument‐breathing species were significantly positively correlated with degree of body flattening or elongation during ontogeny, as expected from surface area theory, but contradicting the negative correlations predicted by resource‐transport network models. This finding explains strong deviations from predictions of widely adopted theory, and underpins a new explanation for mass‐invariant metabolic scaling during ontogeny in animals and plants.

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Feeding and overwintering of Antarctic krill across its major habitats: The role of sea ice cover, water depth, and phytoplankton abundance - Katrin Schmidt; Angus Atkinson; David W. Pond; Louise C. Ireland (Limnology and Oceanography, 2014)
Antarctic krill ( Euphausia superba ) were sampled in contrasting habitats: a seasonally ice‐covered deep ocean (Lazarev Sea), ice‐free shelves at their northern range (South Georgia) and the Antarctic Peninsula (Bransfield Strait), and shelf and oceanic sites in the Scotia Sea. Across 92 stations, representing a year‐round average, the food volume in krill stomachs comprised 71 ± 29% algae, 17 ± 21% protozoans, and 12 ± 25% metazoans. Fatty acid trophic markers showed that copepods were consistently part of krill diet, not a switch food. In open waters, both diatom and copepod consumption increased with phytoplankton abundance. Under sea ice, ingestion of diatoms became rare, whereas feeding on copepods remained constant. During winter, larvae contained high but variable proportions of diatom markers, whereas in postlarvae the role of copepods increased with krill body length. Overwintering differed according to habitat. Krill from South Georgia had lower lipid stores than those from the Bransfield Strait or Lazarev Sea. Feeding effort was much reduced in Lazarev Sea krill, whereas most individuals from the Bransfield Strait and South Georgia contained phytoplankton and seabed detritus in their stomachs. Their retention of essential body reserves indicates that krill experienced most winter hardship in the Lazarev Sea, followed by South Georgia and then Bransfield Strait. This was reflected in the delayed development from juveniles to adults in the Lazarev Sea. Circumpolar comparisons of length frequencies suggest that krill growth conditions are more favorable in the southwest Atlantic than in the Lazarev Sea or off East Antarctica because of longer phytoplankton bloom periods and rewarding access to benthic food.

An intra-specific linkage map of lettuce (Lactuca sativa) and genetic analysis of postharvest discolouration traits - Laura D. Atkinson; Leah K. McHale; María José Truco; Howard W. Hilton; James Lynn; Johan W. Schut; Richard W. Michelmore; Paul Hand; David A. C. Pink (Theoretical and Applied Genetics, 2013)

Conflicting and Complementary Ethics of Animal Welfare Considerations in Reintroductions - LAUREN A. HARRINGTON; AXEL MOEHRENSCHLAGER; MERRYL GELLING; ROB P. D. ATKINSON; JOELENE HUGHES; DAVID W. MACDONALD (Conservation Biology, 2013)
Despite differences in focus, goals, and strategies between conservation biology and animal welfare, both are inextricably linked in many ways, and greater consideration of animal welfare, although important in its own right, also has considerable potential to contribute to conservation success. Nevertheless, animal welfare and animal ethics are not always considered explicitly within conservation practice. We systematically reviewed the recent scientific peer‐reviewed and online gray literature on reintroductions of captive‐bred and wild‐caught animals (mammals, birds, amphibians, and reptiles) to quantify the occurrence of animal welfare issues. We considered monitoring that could be indicative of the animal's welfare status and supportive management actions that could improve animal welfare (regardless of whether the aim was explicitly animal‐welfare orientated). Potential welfare issues (of variable nature and extent) were recorded in 67% of 199 projects reviewed; the most common were mortality >50%, dispersal or loss of animals, disease, and human conflict. Most (>70%) projects monitored survival, 18% assessed body condition, and 2% monitored stress levels. Animal welfare, explicitly, was referred to in 6% of projects. Supportive actions, most commonly use of on‐site prerelease pens and provision of supplemental food or water, were implemented in 79% of projects, although the extent and duration of support varied. Practitioners can address animal‐welfare issues in reintroductions by considering the potential implications for individual animals at all stages of the release process using the decision tree presented. We urge practitioners to report potential animal‐welfare issues, describe mitigation actions, and evaluate their efficacy to facilitate transparent evaluation of common moral dilemmas and to advance communal strategies for dealing with them. Currently, comparative mortality rates, health risks, postrelease stress, effectiveness of supportive measures, and behavior of individuals warrant further research to improve animal welfare in reintroductions and to increase success of such projects. Ética Conflictiva y Complementaria al Considerar el Bienestar Animal en Reintroducciones

Conformation and stability properties of B17: II. Analytical investigations using differential scanning calorimetry - Hassan M. Khachfe; David Atkinson (European Biophysics Journal, 2013)

An enzyme activity capable of endotransglycosylation of heteroxylan polysaccharides is present in plant primary cell walls - Sarah L. Johnston; Roneel Prakash; Nancy J. Chen; Monto H. Kumagai; Helen M. Turano; Janine M. Cooney; Ross G. Atkinson; Robert E. Paull; Roshan Cheetamun; Antony Bacic; David A. Brummell; Roswitha Schröder (Planta, 2013)

Conformation and stability properties of B17: I. Analytical investigations using circular dichroism - Hassan M. Khachfe; David Atkinson (European Biophysics Journal, 2012)

Synoptic forcing of wave states in the southeast Chukchi Sea, Alaska, at an offshore location - Oceana P. Francis; David E. Atkinson (Natural Hazards, 2012)

Synoptic forcing of wave states in the southeast Chukchi Sea, Alaska, at nearshore locations - Oceana P. Francis; David E. Atkinson (Natural Hazards, 2012)

The Arctic Coastal Dynamics Database: A New Classification Scheme and Statistics on Arctic Permafrost Coastlines - Hugues Lantuit; Pier Paul Overduin; Nicole Couture; Sebastian Wetterich; Felix Aré; David Atkinson; Jerry Brown; Georgy Cherkashov; Dmitry Drozdov; Donald Lawrence Forbes; Allison Graves-Gaylord; Mikhail Grigoriev; et al. (Estuaries and Coasts, 2012)

DNA sequence requirements for hobo transposable element transposition in Drosophila melanogaster - Yu Jung Kim; Robert H. Hice; David A. O’Brochta; Peter W. Atkinson (Genetica, 2011)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Neurocognitive functioning in acute or early HIV infection - David J. Moore; Scott L. Letendre; Sheldon Morris; Anya Umlauf; Reena Deutsch; Davey M. Smith; Susan Little; Alexandra Rooney; Donald R. Franklin; Ben Gouaux; Shannon LeBlanc; Debra Rosario; et al. (Journal of NeuroVirology, 2011)

Environmental Factors Affecting Ultraviolet Photodegradation Rates and Estrogenicity of Estrone and Ethinylestradiol in Natural Waters - Susanna K. Atkinson; Vicki L. Marlatt; Lynda E. Kimpe; David R. S. Lean; Vance L. Trudeau; Jules M. Blais (Archives of Environmental Contamination and Toxicology, 2011)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

The intraspecific scaling of metabolic rate with body mass in fishes depends on lifestyle and temperature - Shaun S. Killen; David Atkinson; Douglas S. Glazier (Ecology Letters, 2010)
Ecology Letters (2010) 13: 184–193 Abstract Metabolic energy fuels all biological processes, and therefore theories that explain the scaling of metabolic rate with body mass potentially have great predictive power in ecology. A new model, that could improve this predictive power, postulates that the metabolic scaling exponent ( b ) varies between 2/3 and 1, and is inversely related to the elevation of the intraspecific scaling relationship (metabolic level, L ), which in turn varies systematically among species in response to various ecological factors. We test these predictions by examining the effects of lifestyle, swimming mode and temperature on intraspecific scaling of resting metabolic rate among 89 species of teleost fish. As predicted, b decreased as L increased with temperature, and with shifts in lifestyle from bathyal and benthic to benthopelagic to pelagic. This effect of lifestyle on b may be related to varying amounts of energetically expensive tissues associated with different capacities for swimming during predator–prey interactions.

Local adaptation to higher temperatures reduces immigration success of genotypes from a warmer region in the water flea Daphnia - WENDY VAN DOORSLAER; JOOST VANOVERBEKE; CATHY DUVIVIER; SARAH ROUSSEAUX; MIEKE JANSEN; BASTIAAN JANSEN; HEIDRUN FEUCHTMAYR; DAVID ATKINSON; BRIAN MOSS; ROBBY STOKS; LUC DE MEESTER (Global Change Biology, 2009)
There is growing awareness that microevolutionary dynamics may alter ecological processes. Rising temperatures under global change are expected to open windows for establishment of species and genotypes from warmer regions. Yet, microevolutionary tracking of temperature change by local populations may reduce establishment success of these immigrants. We exposed a UK population of the water flea, Daphnia magna , to two temperature regimes during a 1.5‐year experimental evolution trial, and subsequently compared competitive strength of non‐warm‐adapted and warm‐adapted D. magna in competition with French genotypes. Our results indicate that local microevolutionary responses to global warming may reduce establishment success of immigrant genotypes that are preadapted to warmer climate. Simulation modeling shows that microevolution results in a reduced likelihood and speed of displacement of local populations by immigrant genotypes under realistic immigrant/resident ratios. We conclude that local evolutionary dynamics may shift the relative impact of local and regional processes in response to global change.

Short‐term temperature change may impact freshwater carbon flux: a microbial perspective - DAVID J. S. MONTAGNES; GARETH MORGAN; JAN E. BISSINGER; DAVID ATKINSON; THOMAS WEISSE (Global Change Biology, 2008)
Small freshwater bodies are abundant and economically and ecologically important on a global scale. Within these, protozoa play an important role in structuring planktonic food webs and sequestering CO 2 . We hypothesized that short‐term (∼20 days) fluctuations, of 2–10 °C, will significantly alter carbon flux associated with predator–prey interactions within the microbial planktonic food web. We examined the model ciliate, Urotricha farcta , which is abundant and common; it was fed the autotrophic flagellate Cryptomonas sp., which is also common. Laboratory experiments were conducted over relevant ranges: 8–24 °C; 0–2 × 10 5 prey mL −1 . Mechanistic‐phenomenological multiple regressions were developed and fit to the data to obtain relationships for (1) growth rate and volume changes of the flagellate vs. temperature and (2) growth rates, grazing, and cell volume change of the ciliate vs. temperature and prey concentration. Responses revealed interaction between temperature and prey levels on all ciliate parameters, indicating it is inappropriate to apply simple temperature corrections (e.g. Q 10 ) to such functions. The potential impact of such temperature changes on carbon flux was illustrated using a simple ciliate–flagellate predator–prey model, with and without the top grazer, Daphnia , added. The model indicated that predator–prey pulses occurred over 20 days, with the ciliate controlling the prey population. For ciliates and prey, carbon production peaked at 20 °C and rapidly decreased above and below this maximum; differences between minimum and maximum were approximately fourfold, for both prey and ciliate, with low levels at 25–30 °C and 10–15 °C. Including literature data to parameterize, the influence of the grazer Daphnia did not alter the prediction that the ciliate may control short‐term flagellate pulses and temperature will influence these in a nonintuitive fashion.

Predicting marine phytoplankton maximum growth rates from temperature: Improving on the Eppley curve using quantile regression - Jan E. Bissinger; David J. S. Montagnes; Jonathan harples; David Atkinson (Limnology and Oceanography, 2008)
The Eppley curve describes an exponential function that defines the maximum attainable daily growth rate of marine phytoplankton as a function of temperature. The curve was originally fitted by eye as the upper envelope of a data set, and despite its wide use, the reliability of this function has not been statistically tested. Our analysis of the data using quantile regression indicates that while the curve appears to be a good estimate of the edge of the data, it may not be reliable because the data set is small ( n = 162). We construct a contemporary, comprehensive data set ( n = 1,501) and apply an objective approach, quantile regression, to estimate its upper edge (99th quantile). This analysis yields a new predictive equation, µ max = 0.81e 0.0631T , that describes the maximum specific growth rates (µmax, d −1 ) of marine phytoplankton as a function of temperature ( T , ° C ). The Liverpool phytoplankton database (LPD) curve is higher than the Eppley curve across all temperatures, and at temperatures below 19°C, the Eppley curve falls below the lower 95% confidence interval of the LPD curve. However, the LPD Q 10 value (1.88) is identical to that of the Eppley curve and thus supports the use of models that incorporate this as an estimate of phytoplankton growth‐rate response to temperature change. To assess the potential effect of the LPD curve on primary production, we embedded the LPD function into a one‐dimensional numerical model of a temperate, pelagic ecosystem. This analysis suggests that models using the Eppley function will underestimate primary production by as much as 30%.

Unusual new Chaetosphaeria species from New Zealand: Intrafamilial diversity and elucidations of the Chaetosphaeriaceae ‐Lasiosphaeriaceae relationship (Sordariomycetes, Ascomycotina) - Toni J. Atkinson; Andrew N. Miller; Sabine M. Huhndorf; David A. Orlovich (New Zealand Journal of Botany, 2007)
Chaetosphaeria albida, C. bombycina , and C. metallicans are described and compared with other Chaetosphaeria taxa using morphological and molecular methods. The fresh ascomata of C. albida are almost white, translucent, and aereolate; they are papillate with a distinctive 4‐layered peridium, and the ascospores are scolecosporous, multiseptate, and hyaline. C. bombycina is similar, but the fresh ascomata are light fawn‐grey with a reflective silken appearance, non‐papillate, and the similar peridium is 3‐layered. C. metallicans has ascomata which are blue‐black, shiny and metallic when fresh; the thick peridium is heavily melanised, and the ascospores are straight to allantoid, 3‐septate, and hyaline. The scolecosporous ascospores of C. albida and C. bombycina would have traditionally referred these taxa to Lasiosphaeria . However, like C. metallicans , they lack a peridial tomentum, and have asci with light‐refractive, non‐amyloid apical rings, without a sub‐apical globule. Despite the major differences in spore shape and ascomal wall structure, analyses of the LSU and ITS regions of ribosomal DNA suggest that genetically all three fall within Chaetosphaeria , near to C. raciborskii , and in a sister clade to the type species C. innumera . The placement of these species considerably expands current morphological conceptions of Chaetosphaeria , particularly in terms of ascomal wall appearance and structure, and confirms the existence of a scolecosporous group within the genus. in the search for morphological characters which mimic genetic relationships, this study further elucidates the relationship between the Chaetosphaeriaceae and the Lasiosphaeriaceae.

Occurrence and Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in Bolgoda and Beira Lakes, Sri Lanka - K. A. S. Pathiratne; O. C. P. De Silva; David Hehemann; Ian Atkinson; Robert Wei (Bulletin of Environmental Contamination and Toxicology, 2007)

Response of macroinvertebrates to warming, nutrient addition and predation in large-scale mesocosm tanks - Heidrun Feuchtmayr; Dermot McKee; Ian F. Harvey; David Atkinson; Brian Moss (Hydrobiologia, 2007)

Synchronicity in Climate and Vegetation Transitions Between Europe and North America During the Holocene - K. Gajewski; André E. Viau; Michael Sawada; David E. Atkinson; Philippe Fines (Climatic Change, 2006)

Have the Harmful Effects of Introduced Rats on Islands been Exaggerated? - David R. Towns; Ian A. E. Atkinson; Charles H. Daugherty (Biological Invasions, 2006)

hAT element population genetics in Anopheles gambiae s.l. in Mozambique - David A. O’Brochta; Ramanand A. Subramanian; Jamison Orsetti; Edward Peckham; Nicole Nolan; Peter Arensburger; Peter W. Atkinson; Derek J. Charlwood (Genetica, 2006)

Observed storminess patterns and trends in the circum-Arctic coastal regime - David E. Atkinson (Geo-Marine Letters, 2005)

Arctic Coastal Dynamics (ACD): an introduction - Volker Rachold; Feliks E. Are; David E. Atkinson; Georgy Cherkashov; Steven M. Solomon (Geo-Marine Letters, 2005)

Diversity of arbuscular mycorrhizal fungi colonising roots of the grass species Agrostis capillaris and Lolium perenne in a field experiment - Armelle Gollotte; Diederik van Tuinen; David Atkinson (Mycorrhiza, 2004)

Establishing the Canadian Community Monitoring Network - Graham Whitelaw; Hague Vaughan; Brian Craig; David Atkinson (Environmental Monitoring and Assessment, 2003)

Why phase II trials in cervical chemoprevention are negative: what have we learned? - Michele Follen; Anne-Thérèse Vlastos; Frank L. Meyskens; E. Neely Atkinson; David Schottenfeld (Cancer Causes & Control, 2002)

Physical and chemical limnology of 204 lakes from the Canadian Arctic Archipelago - Paul B. Hamilton; Konrad Gajewski; David E. Atkinson; David R.S. Lean (Hydrobiologia, 2001)

The influence of climate change scenarios on populations of the mayfly Cloeon dipterum - Dermot McKee; David Atkinson (Hydrobiologia, 2000)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Integration specificity of the hobo element of Drosophila melanogaster is dependent on sequences flanking the integration site - Kenneth J. Saville; William D. Warren; Peter W. Atkinson; David A. O'Brochta (Genetica, 1999)

Transgenic Arabidopsis leaf tissue expressing a modified oryzacystatin shows resistance to the field slug Deroceras reticulatum (Müller) - Anthony J. Walker; Peter E. Urwin; Howard J. Atkinson; Philip Brain; David M. Glen; Peter R. Shewry (Transgenic Research, 1999)

Filtration enhances suspended sediment deposition from surface water to granular permeable beds - David C J. D. Royal; Marcus I. Bursik; Joseph F. Atkinson; Joseph V. Depinto (Water, Air, & Soil Pollution, 1997)

Filtration Enhances Suspended Sediment Deposition from Surface Water to Granular Permeable Beds - David C.J.D. Hoyal; Marcus I. Bursik; Joseph F. Atkinson; Joseph V. Depinto (Water, Air, & Soil Pollution, 1997)

TheHermes element fromMusca domestica can transpose in four families of cyclorrhaphan flies - Abhimanyu Sarkar; Craig J. Coates; Steven Whyard; Ute Willhoeft; Peter W. Atkinson; David A. O'Brochta (Genetica, 1997)

The allopolyploid origin of kiwifruit,Actinidia deliciosa (Actinidiaceae) - Ross G. Atkinson; Guido Cipriani; David J. Whittaker; Richard C. Gardner (Plant Systematics and Evolution, 1997)

The Hermes element from Musca domestica can transpose in four families of cyclorrhaphan flies - Abhimanyu Sarkar; Craig J. Coates; Steven Whyard; Ute Willhoeft; Peter W. Atkinson; David A. O'Brochta (Genetica, 1997)